Muscle-invasive Bladder Cancer in the Elderly Patient With a Focus on Hypofractionated Radiotherapy. Issue 6 (June 2021) - Slevin, F.; Henry, A.M.
Abstract: Muscle-invasive bladder cancer is most frequently diagnosed in older patients and the presence of multimorbidity and frailty is common. This means that many patients are unsuitable for definitive treatment with radical cystectomy/(chemo)radiotherapy and are at risk of poor survival outcomes and considerable disease-related morbidity. Screening tools for functional status may be useful to determine the most appropriate treatment for an older person and to identify patients most likely to benefit from comprehensive geriatric assessment and its targeted prehabilitation interventions. For patients unsuitable for definitive treatment, ultrahypofractionated radiotherapy schedules may provide good local control with acceptable toxicity. Short fractionated palliative radiotherapy schedules can provide effective symptom control for patients unsuitable for longer courses of treatment. Highlights: Most patients diagnosed with muscle-invasive bladder cancer are elderly. Comorbidity and frailty are common and may preclude definitive treatment. Hypofractionated radiotherapy may provide good local control and symptomatic relief.